Analysis the quality of critical thinking and creativity questions in high school biology subjects with the Rasch model - Tasya Novian Indah Sari; Anna Rakhmawati (Universitas Muhammadiyah Malang, 2024)
A good instrument is an instrument that can measure students' abilities accurately. The research aims to analyze the quality of critical thinking and creativity items on water pollution material in terms of validity, reliability, and level of difficulty using the Rasch model. The research used a quantitative descriptive method involving biology learning experts and 173 class X high school students. The research was carried out in December 2023-January 2024. The data collection method used expert assessment sheets and critical thinking and creativity essay questions. Data were analyzed using the Rasch model assisted by Quest. The results showed that of the 10 critical thinking essay questions, 3 questions were invalid, while of the 8 creativity essay questions, 1 question was invalid based on the suitability of the INFIT MNSQ and OUTFIT T scores. The results of the reliability test with Cronbach’s alpha showed that the reliability value of the critical thinking instrument was 0.74 and creativity 0.79. Average difficulty level of questions with threshold values in the medium and difficult categories. Overall, the instrument was feasible and question items that did not fit the Rasch model were removed.